Analysis of the retrieval times of a centralised transport service, New South Wales, Australia. Issue 4 (16th October 2008) - Abdel-Latif, M E; Berry, A
Abstract : Objectives: To examine the transport times of immediate and emergency retrievals for neonatal and paediatric patients retrieved by ground and air from general hospitals to tertiary centres. Designs: We conducted a database review of the records of 17 011 requests for retrieval to a centralised transport service in New South Wales and the Australian Capital Territory, Australia from 2000 to 2006. Results: Immediate and emergency retrievals included 4575 (43.7%) neonatal and 5887 (56.3%) paediatric retrievals. The median stabilisation time was 97 min for neonatal compared with 50 min for paediatric retrievals. Neonatal retrievals had a significantly longer stabilisation time (approx ×2), handover time (approx ×1.2) and mission time (approx ×1.3) compared to paediatric retrievals. Conclusions: Establishing reference times for the transport process is a valuable quality assurance tool. Such data will be valuable for staff and budgeting purposes and for evaluating new interventions that reduce retrieval times.